The biology of Marchantia polymorpha subsp. ruderalis Bischl. & Boissel. Dub in nature - Duckett, Jeffrey G.; Pressel, Silvia; Kowal, Jill (Frontiers in Plant Science, 2024)
Introduction Though used as the model liverwort in culture for several decades, the biology of Marchantia polymorpha subsp. ruderalis in nature has never been documented in detail in a single account. Methods Here we synthesize routine field observations documented with hundreds of images of M. ruderalis colonies (or groups) showing sex differentiation over 3 years on two populations of M. ruderalis after major heathland fires in 2020. Results Initial post-fire establishment is from airborne spores rather than a spore bank but thereafter spread is via gemmae which have less exacting germination requirements. Young sporelings are highly gemmiferous but gemmae production becomes less frequent after sex organ formation. Over the course of a year there are up to three waves of carpocephalum production with the overwhelming majority of antheridiophores appearing 2-3 months ahead of the archegoniophores though no differences in growth rates were apparent between male and female thalli. Spermatozoids are produced almost continuously throughout the year, whilst sporophyte maturation is restricted to the summer months. Discussion Because of the asynchrony between antheridiophore and archegoniophore production a 1:1 sex ratio is only apparent over this period. The spring months see an excess of males with more females in the summer. An almost 100% fertilization rate, with fertilization distances of up to 19 m far exceeding those in all other bryophytes, is attributed to vast spermatozoid production for most of the year, dispersal on surface oil films between thalli and highly effective intra-thallus spermatozoid transport via the pegged-rhizoid water-conducting system. Archegoniophores do develop on female-only populations but have shorter stalks than those where fertilization has occurred. Eventual disappearance post fires is attributed to a fall in topsoil nutrient levels preventing new sporeling establishment and competition from Ceratodon purpureus and Polytrichum spp. A major drought in the summer of 2022 almost wiped out the heathland Marchantia populations but all the other bryophytes survived.